MENCERDASKAN ANAK BANGSA MELALUI PENDEKATAN PEMBELAJARAN PENDIDIKAN ANAK USIA DINI - Zaenab, Siti; Sueca, I Nyoman (PRATAMA WIDYA : JURNAL PENDIDIKAN ANAK USIA DINI, 2018)
AbstractGovernment policy in a program with education care, and early childhood development (PAUD) as a concrete manifestation of the government’s commitment is in the document “National Program for Indonesian Children (PNBAI). The important value of early childhood (early childhood) period for the growth and development ofchildren in the future, is increasingly realized by parents. This growing awareness raises an escalation of interest for quality early childhood education that can meet their expectations. The intelligence that occurs in children, cognitive theory and psychoanalytic theory is very important in supporting children play a reference in determining the stage of child development in terms of cognitive, afktif, psikomotorik, language, and social emotional. Early childhood learning approach as the main arena in instilling knowledge of Indonesian children aged 4-5 years is done with various setrategi as a skill in mengartur appropriate learning, in order to achieve maximum results which is the hope of society. In some rural communities, many still do not take advantage of their early childhood education opportunities, many factors affect the economy, parents, and the distance to school. During this education from tingkan PAUD to kindergarten in rural areas almost mostly built by the party suwasta in the form of the foundation. This is something that needs to get the attention of the central government to the district level. Keywords: To hatch the nation’s childrenAbstrakKebijakan pemerintah dalam sebuah program dengan pengasuhan pendidikan, dan pengembangan anak usia dini (PAUD) sebagai wujud nyata komitmen pemerintah adalah yang temuat dalam dokumen berupa “Program Nasional Bagi Anak Indonesia (PNBAI). Nilai penting periode anak usia dini (PAUD) bagi pertumbuhan dan perkembangan anak dimasa yang akan datang, semakin disadari oleh orang tua. Kesadaran yang terus tumbuh tersebut menimbulkan eskalasi/pertambahan minat terhadap pendidikan anak usia dini yang berkualitas yang bisa memenuhi harapan mereka. Kecerdasan yang terjadi pada anak-anak, teori kognitif dan teori psikoanalitis sangat penting dalam menunjang main anak menjadi acuan dalam menentukan tahap perkembangan anak baik dari segi kognitif, afktif, fisikomotorik, bahasa, maupun sosial emosional. Pendekatan pembelajaran anak usia dini sebagai ajang utama dalam penanamkan pengetahuan terhadap anak Indonesia yang berumur 4-5 tahun dilakukan dengan berbagai setrategi sebagai sebuah ketrampilan dalam mengartur pembelajaran yang sesuai, agar mencapai hasil maksimal yang merupakan harapan masyarakat. Di beberapa masyarakat daerah pedesaan masih banyak belum memanfaatkan kesempatannya untuk membeikan pendidikan usia dini terhadap anak-anak mereka, hal ini banyak faktor yang mempengaruhi misalkan, ekonomi, kesibukan orang tua maupun jarak